2018
DOI: 10.1111/eff.12425
|View full text |Cite
|
Sign up to set email alerts
|

High intraspecific variability in morphology and diet in tropical stream fish communities

Abstract: Functional diversity of fish communities has been measured according to (a) interspecific variability, assuming that intraspecific variability is negligible, or (b) morphological differences, as good descriptors of complex functions, such as diet. These two assumptions have been scarcely tested on the individual level, especially in species‐rich tropical ecosystems. Here, we adapted intraspecific specialisation (ISpe) and intraspecific originality indices (IOri) to assess complementary components of intraspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 78 publications
0
23
0
12
Order By: Relevance
“…Cada abordagem contribui de forma única para o avanço do conhecimento ecológico, desde respostas mais descritivas a respeito de uma população ou comunidade local (e.g. Brito et al 2019, Manna et al 2019) até respostas mais teóricas que ajudam a explicar dinâmicas ecológicas e/ou evolutivas (e.g. Matthews et al 2010).…”
Section: Características Mensuradas No Grupo Dos Peixesunclassified
See 3 more Smart Citations
“…Cada abordagem contribui de forma única para o avanço do conhecimento ecológico, desde respostas mais descritivas a respeito de uma população ou comunidade local (e.g. Brito et al 2019, Manna et al 2019) até respostas mais teóricas que ajudam a explicar dinâmicas ecológicas e/ou evolutivas (e.g. Matthews et al 2010).…”
Section: Características Mensuradas No Grupo Dos Peixesunclassified
“…No entanto, apenas aqueles artigos que relacionaram aspectos da variação intraespecífica com as estratégias tróficas em populações e/ou comunidades foram considerados, restando 22 artigos. Para exemplificar a existência de variação intraespecífica dentro de populações de peixes, dados referentes a duas espécies do gênero Deuterodon, que coexistem em um riacho costeiro de Mata Atlântica, revelam diferenças na dieta com alta variação intraespecífica em ambas as espécies (Manna et al 2019). Deuterodon hastatus utiliza insetos aquáticos como principal fonte alimentar, enquanto Deuterodon taeniatus, matéria vegetal alóctone.…”
Section: Tipos De Variação Intraespecíficaunclassified
See 2 more Smart Citations
“…It is interesting to note that Sides and Sloat (2014) found that species with greater intraspecific variation in specific leaf area (SLA) have wider ecological breadth. Because of its potential role in modulating the responses of plant species to environmental changes, greater intraspecific functional variability may enable species to adjust to a wider range of competitive and abiotic conditions (Sides and Sloat, 2014;Manna et al, 2019).…”
Section: Effects Of Dispersal Modes and Seed Mass On The Distributionmentioning
confidence: 99%